Liposomes vs. Probiosomes: A Novel Approach for Targeted Drug Delivery - Riccardi, Bruno; Resta, Sergio; Resta, Giacomo (Discoveries in Agriculture and Food Sciences, 2024)
Liposomal technology is a specialized branch of nanotechnology, which has allowed to improve many of the drawbacks and limitations of traditional drug therapy. By the use of this technology, in fact, you can produce very useful carriers for those drugs that have a low therapeutic index or reduced bioavailability, to make them equipped with a selective tropism for target organs. The upgrade of liposomal technology is represented by Probiosomas. Probiosomes are an innovative and promising nanocarrier system that has garnered significant attention in the field of drug delivery and therapeutics. These biocompatible lipid-based vesicles have emerged as a versatile platform for encapsulating and delivering a wide range of therapeutic agents, including drugs, genes, and diagnostic agents. This paper provides a comprehensive overview of probiosomes, including their structure, properties, fabrication methods, and applications in drug delivery and therapy. We also discuss the advantages, challenges, and future prospects of probiosomes in the context of personalized medicine and targeted therapies.